Characteristics of chemical weathering and water–rock interaction in Lake Nyos dam (Cameroon): Implications for vulnerability to failure and re-enforcement. (January 2015) - Fantong, Wilson Y.; Kamtchueng, Brice T.; Yamaguchi, Kohei; Ueda, Akira; Issa,; Ntchantcho, Romaric; Wirmvem, Mengnjo J.; Kusakabe, Minoru; Ohba, Takeshi; Zhang, Jing; Aka, Festus T.; Tanyileke, Gregory; et al.
Highlights: Dam spring is a mixture of rain and Lake water. With chemical weathering the dam is save, but other natural processes maintain the potentials of instant collapse. Minimum dam width to resist hydrostatic pressure is 19 m. Dam monitoring is imperative. Abstract: For the first time, comprehensive study of hydrogeochemistry of water seeps, role of chemical weathering on dam failure, estimation of minimum width of dam to resist failure and simulation of changes in dissolved ions and secondary mineral was conducted on the Lake Nyos dam. The salient results and conclusions were; the dam spring water represented a mixture of 60–70% rainwater and 30–40% Lake water (from 0 to −40 m). The chemistry of the observed waters was Ca–HCO3 for rainwater, Ca–Mg–HCO3 in boreholes, and Mg–Ca–HCO3 − for spring water. The relative rate at which ions dissolved in water was HCO3 − > Mg 2+ > Ca 2+ > Na + > SiO2 > K + > NO3 − > SO4 2 − > Cl − . Weathering of rocks resulted in the formation of clay minerals such as kaolinite and smectite. Relative mobility of elements compared to Alumina (Al2 O3 ) indicated that in monzonites there was a loss of CaO, Na2 O, K2 O, P2 O5 and gain of SiO2, Fe2 O3, TiO2, MnO and MgO, while in basalts there was a loss of SiO2, Fe2 O3, Ca2 O, NaO, MgO and gain of TiO2, K2 O and P2 O5 . Values of chemical alteration index that ranged from 49 to 82 suggest a weak to intermediate categories of chemical weathering that occurred at a rate of 5.7 mm/year. Paired to that rate, which suggests that the dam is not vulnerable to failure at the previously thought time scale, some other processes (physical weathering, secondary mineral formation and lake overflow) can cause instant failure. Hydrostatic pressure of 1.6 GN generated by Lake water can be supported only when the width of the dam is greater than 19 m. PHREEQC-based simulation for 10 years indicates decoupling of Ca and Mg, and Na and Mg. Multidisciplinary monitoring of the dam is advocated.